Radicalization And Violent Extremism Of Indonesian Children - Diany Khaeria Rahmi; Iqrak Sulhin (Eduvest - Journal of Universal Studies, 2024)
Several regions in Indonesia such as Aceh, Central Sulawesi, NTB and Maluku have experienced conflict situations with ethnic, religious, racial and inter-group backgrounds. This background carries the risk of conflict triggering acts of violence-based extremism and radicalism which of course have an impact on the development of children born and growing up in conflict areas. Extremist behavior that leads to radical actions and acts of terror involving children has occurred in Indonesia in cases of family suicide bombings. Effective interventions are needed to control the potential for radicalization in children. This research uses a qualitative approach using data collection methods through literature studies to understand and detail the dynamics related to children involved in radicalism and violent extremism, especially in the context of acts of terrorism in Indonesia. Data from literature studies are used to analyze the role of family, environment and education in building children's resilience against the threat of radicalism. Through a qualitative approach, this research explores the practice of social control modes, the role of Restorative Justice (RJ), and its implications. Analysis of the classification of children involved in terrorism based on factors such as affiliation, province of origin, age, level of radicalization, and conviction provides an in-depth understanding of their characteristics and patterns of involvement. The research results provide an overview of the potential threat of exposure to radicalism and violence-based extremism targeting children.